The competitive advantages of organisations in Zimbabwe’s hospitality industry: A case of two organisations - Farai Ncube; Peter Sibanda; Langtone Maunganidze (Scholarlink Research Institute, 2023)
The Zimbabwe economy has recently been plagued by various forms of industrial fragility characterized by unprecedented hyper-inflation, low levels of investment and under capitalization in many sectors particularly the hospitality industry following the hotly contested land reform program in 2000 and series of disputed parliamentary elections that followed. However the situation has improved following the formation of the Government of National Unity (GNU) in February, 2009 and the adoption of multi-currency system to arrest the shortage of foreign currency and restore stability inboth productive and consumption sectors of the economy. One such sector has been the hospitality industry, which represents one of the fastest growing sectors in the country. Since then there has been an improvement in performance in the sector as evidenced by increased Food Covers, Average Room Rates, and Average Spent per Cover and Revenue per Available Room.This article uses the Co-evolution Theory to explore the determinants of competitive advantage in the hospitality sector in Zimbabwe specifically focusing on two groups of hotels from which we selected one per group herein labeled hotels A and B. The research design was predominantly qualitative and data was collected using interviews and questionnaires distributed to 100 participants selected by stratified availability sampling. Themajor findings indicated that while service delivery, hotel location, hotel capacity, hotel products and pricing and infrastructural capabilities were considered generic drivers to competitive edge, people issues particularly employee engagement, were central to the equation. The article recommends for more focus on swift service delivery, massive training, good customer care, recapitalisation, IT focus, product differentiation and the provision of flexible rates to sustain competitive advantage. Thus the paper strongly challenges companies in the hospitality industry in Zimbabwe to take note of the potential the industry has in determining the future of the country as a major revenue centre and equally equip managers with arsenals to ensure a competitive edge for enhancing the shareholder wealth.